Long noncoding RNA mediates stroke‐induced neurogenesis. (2nd May 2020) - Fan, Baoyan; Pan, Wanlong; Wang, Xinli; Wei, Min; He, Annie; Zhao, Anna; Chopp, Michael; Zhang, Zheng Gang; Liu, Xian Shuang
Abstract: Neurogenesis contributes to poststroke recovery. Long noncoding RNAs (lncRNAs) participate in the regulation of stem cell self‐renewal and differentiation. However, the role of lncRNAs in stroke‐induced neurogenesis remains unknown. In this study, we found that H19 was the most highly upregulated lncRNA in neural stem cells (NSCs) of the subventricular zone (SVZ) of rats subjected to focal cerebral ischemia. Deletion of H19 suppressed cell proliferation, promoted cell death, and blocked NSC differentiation. RNA sequencing analysis revealed that genes deregulated by H19 knockdown were those that are involved in transcription, apoptosis, proliferation, cell cycle, and response to hypoxia. H19 knockdown significantly increased the transcription of cell cycle‐related genes including p27, whereas overexpression of H19 substantially reduced expression of these genes through the interaction with chromatin remodeling proteins EZH2 and SUZ12. Moreover, H19 regulated neurogenesis‐related miRNAs. Inactivation of H19 in NSCs of ischemic rats attenuated spontaneous functional recovery after stroke. Collectively, our data provide novel insights into the epigenetic regulation of lncRNAs in stroke‐induced neurogenesis. Abstract : The role of lncRNA H19 in stroke‐induced neurogenesis remains unknown. Using CRISPR‐Cas9 genome editing in adult neural stem cells (NSCs), H19 was knocked down, and suppresses the proliferation and the neuronal differentiation of NSCs. Intraventricular injection of AVV viral vector which contained Ascl1‐Cre recombinase and sgRNA to floxed cas9 knockin mice induces cognitive deficits.